KETERASINGAN TOKOH UTAMA DALAM NOVEL SEPORSI MIE AYAM SEBELUM MATI KARYA BRIAN KHRISNA: KAJIAN PSIKOLOGI SASTRA - Saptiana Sulastri; Mellany Rahmawaty; Rajwa Ain Shahada; Riska Febriani; Yulita Ningsih (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examines the alienation of the main character in Brian Khrisna's novel Seporsi Mie Ayam Sebelum Mati (A Bowl of Chicken Noodles Before Death). The problem in this study is how the main character experiences alienation in the story. The focus of the study covers three aspects of alienation, namely the character's alienation from himself, the character's alienation from others, and the character's alienation from society. This study aims to describe and analyze the forms of alienation experienced by the main character in the novel. The method used in this study is a qualitative descriptive method with a literary psychology approach using Erich Fromm's theory of alienation. The source of data for this study is the text of the novel Seporsi Mie Ayam Sebelum Mati. The data collection technique was carried out through reading and note-taking, namely by identifying parts of the text that describe the main character's state of alienation. The data was then analyzed by classifying and interpreting the forms of alienation found based on the theory used. The results of the study show that the main character in the novel experiences three forms of alienation. First, alienation from oneself, which is characterized by inner conflict, feelings of loss of direction, and a crisis of meaning in life. Second, alienation from others, which is evident in strained social relationships and the character's difficulty in building emotional closeness. Third, alienation from society, which is evident through the character's.